Tunable color emission based on the activator shell thickness of multilayer core–shell nanoparticles under double NIR excitation. Issue 28 (24th June 2019) - Ba, Zhaojing; Zheng, Yuansuo; Hu, Min; Fu, Lei; He, Yida; Wang, Jing; Zhang, Zhenxi
Abstract : Rare earth luminescent nanomaterials are hot topic due to their unique fluorescence properties. Effective spectral regulation could be achieved by adjusting the coating thickness to affect the energy transfer process in core–shell structure. Abstract : The multicolor up-conversion luminescence of rare earth-doped nanoparticles is of great importance in biological, chemical, and clinical fluorescent diagnosis, and in the display lighting field. In this work, a multilayer core–shell structure, Er@Y@Tm x @Nd ( x = 1, 2, and 3), was designed and prepared using a thermal decomposition method with some modifications. The Er and Tm, which are used as activators, were doped into different layers of the nanoconstruct. The layers were separated by an inert wall of NaYF4, to hinder the cross-relaxation between the activators. Moreover, the introduction of Nd into the nanoconstruct promoted luminescence when irradiated with both 980 and 808 nm laser sources. In addition, the thickness of the Tm containing layer was carefully controlled, leading to distinct nanomaterials with tunable emission light. The fluorescence changed from yellowish green to bluish green and from bluish green to obvious blue when excited at 980 and 808 nm, respectively. However, the fluorescence lifetimes at 475, 540, and 660 nm did not show significant differences after excitation at 980 nm. It was noticed that when different activators were doped into the different layers, the energy transfer process was obviously influenced by the shell thickness, resulting in a big change in the final luminescence color. Hence, these interesting properties can be considered as a straightforward strategy by which to tune the emission light by controlling the thickness of the layer containing the activator, allowing these materials to be used for various applications.